Neonicotinoids in groundwater: presence and fate in two distinct hydrogeologic settings in Ontario, Canada - Browne, D.; Levison, J.; Limay-Rios, V.; Novakowski, K.; Schaafsma, A. (Hydrogeology journal, 2021)
Neonicotinoids are a group of insecticides that are commonly used in agriculture throughout the world. Despite their widespread use, there are significant knowledge gaps related to the presence and fate of neonicotinoids in groundwater. This research explores the environmental parameters governing the transport of the most commonly found neonicotinoids from surface application to deeper groundwater in two distinct hydrogeologic settings. Both of these research sites are located in Ontario, Canada: one has an unconfined, sandy Quaternary aquifer while the other has a fractured, crystalline bedrock aquifer (Canadian Shield) under a thin layer of soil and till. Groundwater sampling was conducted using 18–26 monitoring intervals at each research site during each sampling round (April 2016, July 2016, August 2016, November 2016, and April 2017). Analysis of six neonicotinoids, two fungicides, two herbicides, and one ryanoid insecticide were conducted using liquid chromatography–mass spectrometry (positive electrospray ionization)–tandem mass spectrometry. During the groundwater sampling period, soil sampling was conducted, and a crop survey completed. Results from groundwater sampling found the neonicotinoids clothianidin, imidacloprid, and thiamethoxam with maximum concentrations and detection frequencies above the level of quantitation of 2.09, 0.7, 0.46 μg/L, and 2.2, 0.9, 1.3%, respectively. Numerical analysis revealed that under similar environmental conditions, clothianidin and thiamethoxam are released in a similar pattern that resembles a pulse. Future research into this subject should include a finer sampling timeframe to confirm theories about the pulsing nature of neonicotinoids in groundwater.